1990
DOI: 10.1111/j.2044-8309.1990.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Social facilitation effects in recognition memory

Abstract: This study investigates the effects of observer presence on recognition memory. The number of learning repetitions, the degree of association of category-instance word pairs, and the time interval between acquisition and testing were manipulated. While the basic recognition data conformed well to previous findings in the learning and memory literature, predictions, derived from the drive theory of social facilitation found little support. Instead, study results seem best explained by descriptions of the cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…If Derryberry and Tucker's suggestion is accurate, however, it means that this typical finding also provides support for the cue utilization view of SFI effects! Consistent with this, Hartwick and Nagao (1990) noted that there is little empirical support for the prediction that social presence enhances performance on noncompetitional paired-associate lists. Although Baron et al (1978) found a significant facilitation effect, Berkey and Hoppe (1972), Cottrell et al (1967), Criddle (1971), Guerin (1983), and Kawamura-Reynolds (1977) all failed to support the prediction.…”
Section: An Alternative Attentional Account Of Sfi Effectsmentioning
confidence: 99%
“…If Derryberry and Tucker's suggestion is accurate, however, it means that this typical finding also provides support for the cue utilization view of SFI effects! Consistent with this, Hartwick and Nagao (1990) noted that there is little empirical support for the prediction that social presence enhances performance on noncompetitional paired-associate lists. Although Baron et al (1978) found a significant facilitation effect, Berkey and Hoppe (1972), Cottrell et al (1967), Criddle (1971), Guerin (1983), and Kawamura-Reynolds (1977) all failed to support the prediction.…”
Section: An Alternative Attentional Account Of Sfi Effectsmentioning
confidence: 99%
“…A common arousal mechanism may explain both the accentuation-attenuation and social facilitation-inhibition phenomena (Zajonc, 1980). Research already indicates that arousal influences the way individuals process information (Geen, 1973(Geen, , 1989Hartwick & Nagao, 1990;Wilder & Shapiro, 1989), so arousal might also influence information processing in groups.…”
Section: Accentuation-attenuation Of Cognitive Processesmentioning
confidence: 99%
“…Individuals were seated with one or two other participants in order to control for social facilitation effects (cf. Hartwick & Nagao, 1990). Group members were instructed to work together unless instructed otherwise, and individuals were instructed to work alone.…”
Section: Methodsmentioning
confidence: 99%